IMPLEMENTASI PENGELOLAAN INVENTARIS DAN PENGGUNAAN BARANG PADA KANTOR BIRO UMUM DAN PERLENGKAPAN PROVINSI SULAWESI BARAT - Wirna, Wirna; Ansyari, Muhammad Isa; Nasrulhaq, Nasrulhaq (Universitas Muhammadiyah Makassar, 2022)
ABSTRACTThe purpose of this research is to find out how the implementation of the Inventory and Use of Goods management at the West Sulawesi General Bureau and Equipment. The number of informants is 5 people. The research method used is qualitative with a descriptive type. Data collection techniques through observations, interviews, and documentation. The results of this research showed that there are several problems that make its implementation not optimal namely in the management of State Property is that there is still poor communication of policies for the management of State Property lack of apparatus resources, there are still unscrupulous users os state property who do not have a posstive attitude. Which do not good in managing state property and the bureaucratic structure that still needs to be improved needs to be rearranged in order to optimize the performance and division managing state property at the Office of the General and Equipment Bureau of West Sulawesi.Keywords : Implementation, inventory of management.